1996
DOI: 10.1037/0022-0663.88.2.260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preexisiting beliefs, epistemological beliefs, and need for cognition on interpretation of controversial issues.

Abstract: This study examined the influence of people's beliefs about the certainty of knowledge, the strength of their beliefs about a controversial issue, and their tendency to enjoy effortful thinking on their interpretation of controversial information. Ninety-six undergraduates completed an epistemological beliefs questionnaire (M. Schommer, 1990), the Need for Cognition Scale (J. T. Cacioppo, R. E. Petty, & C. F. Kao, 1984), and indicated the degree to which they believed that HIV causes AIDS. They then read a tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
190
2
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 310 publications
(221 citation statements)
references
References 22 publications
18
190
2
11
Order By: Relevance
“…The results from Mason and Boscolo (2004) support the conclusions that can be drawn from Kardash's and Scholes's (1996) results. In the study from Mason and Boscolo, high school students read a dual-position expository text on genetically modified food and wrote a concluding paragraph for the dual-position text after reading.…”
Section: Conditions Fostering Elaborative Processing Of Conflicting Isupporting
confidence: 81%
See 4 more Smart Citations
“…The results from Mason and Boscolo (2004) support the conclusions that can be drawn from Kardash's and Scholes's (1996) results. In the study from Mason and Boscolo, high school students read a dual-position expository text on genetically modified food and wrote a concluding paragraph for the dual-position text after reading.…”
Section: Conditions Fostering Elaborative Processing Of Conflicting Isupporting
confidence: 81%
“…A number of studies with multiple texts on socioscientific issues found that reader characteristics such as epistemological beliefs (Mason & Boscolo, 2004), belief strength (Kardash & Scholes, 1996;McCrudden & Barnes, 2016) and prior knowledge, and level of education (Wiley, 2005) can moderate text-belief consistency effects. In particular, an advanced epistemological understanding, strong prior knowledge, a higher level of education, and weaker beliefs seem to prevent the occurrence of text-belief consistency effects.…”
Section: Conditions Fostering Elaborative Processing Of Conflicting Imentioning
confidence: 99%
See 3 more Smart Citations